Plataforma de promoção do clima ético positivo em pronto socorro - Lanes, Taís Carpes (2024)
The ethical climate is defined as the perception of health professionals regarding the ethical treatment of work issues, which can be classified as negative or positive. Through negative evaluation, the ethical climate can affect the quality of care, as well as the health of workers. The objective was to develop, evaluate the quality and apply a computerized platform to promote a positive ethical climate among emergency room health professionals. This is a technological development study, based on the Design Science Research method. This method was organized into six activities, namely: Activity 1 - identify the problem; Activity 2 - define the objective; Activity 3 - design and develop the artifact, in which a scope review was carried out to identify strategies that aim to prospect the ethical environment in health services and the development of the system with its functionalities; Activity 4 - demonstrate the applicability of the strategies found in the scope review, the pilot test of the platform and then, the application of the platform with the target audience in the emergency room. The pilot test of the software was applied to 12 healthcare professionals from the emergency room and, after adjustments, the platform was applied to a larger sample of professionals from the unit. Activity 5 - evaluate the artifact through system quality analysis in accordance with the ISO/IEC 25040:2011 standard and finally activity 6 - communicate the results. The Hospital Ethical Climate Survey-Brazilian Version and sociodemographic and labor characterization instruments were applied. 136 professionals participated in the study, covering all six activities of the research method. Quantitative data analysis occurred using descriptive statistics and qualitative data, based on content analysis. The ethical aspects of Resolution 466/12 were respected. As results, in the scoping review, 13 articles were found in which ethical education strategies, guidelines and codes of ethics, reflection and ethical leadership and ethical consultations were identified, which were evaluated by emergency room professionals regarding their applicability for composition of the platform. The Platform for promoting a positive ethical climate with good technical quality and functional performance was created. The platform was applied in the emergency room, where the general ethical climate (M=3.73; SD=0.60), and its factors ranging from (M=4.2; SD=0.84) to (M=3.23; SD=1.16) were evaluated as positive, however, the doctors factor (M=3.23; SD=1.16) was perceived as negative. Conclusion: It was possible to develop a platform to promote a positive ethical climate for health professionals working in the emergency room, obtaining good technical quality and functional performance.